Pengenalan Dan Penggunaan Edible Coating Dalam Meningkatkan Mutu Buah Dan Sayuran Bagi KWT Anggrek Kecamatan Merbau Mataram Kabupaten Lampung Selatan - Endang Nurcahyani; Yulianty; Emantis Rosa; Hendri Busman (CV. Multi Kreasi Media, 2024)
Fruits and vegetables are horticultural products. This product is easily damaged, so it needs good handling and sufficient attention. So that damage arising from poor handling can be reduced and avoided. Fast handling, sometimes by using materials that are not safe for humans, such as wax. Problems in handling fruits and vegetables occur not only in villages but also in urban areas. So it is necessary to understand and practice for women members of KWT Anggrek in Merbau Mataram District, South Lampung Regency about the use of natural Edible Coatings that are safe for health. The use of Edible Coating is not just giving a thin layer on fruits and vegetables, but it is necessary to find the use of Edible Coating that does not make problems when eaten and of course is environmentally friendly, such as aloe vera, cassava, taro and sweet potato. The pre-test results of the Community Service Participants were 83.2. The post-test results showed an increase with a score of 96.8. This result proves that there is an increase in the understanding and skills of Community Service participants. The existence of this service is expected that KWT Anggrek members can handle fruits and vegetables that are easily damaged and rotten so that they can last longer, namely by using Edible Coating Natural that are easily obtained in the surrounding environment and are environmentally friendly.